2010
DOI: 10.1007/s10597-009-9282-8
|View full text |Cite|
|
Sign up to set email alerts
|

Psychometric Properties of the WHOQOL-BREF in an Iranian Adult Sample

Abstract: To evaluate discriminant validity, reliability, internal consistency, and dimensional structure of the World Health Organization Quality of Life-BREF (WHOQOL-BREF) in a heterogeneous Iranian population. A clustered randomized sample of 2,956 healthy with 2,936 unhealthy rural and urban inhabitants aged 30 and above from two dissimilar Iranian provinces during 2006 completed the Persian version of the WHOQOL-BREF. We performed descriptive and analytical analysis including t-student, correlation matrix, Cronbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 31 publications
5
77
1
6
Order By: Relevance
“…The reliability and validity of the questionnaire of KEYES model was also evaluated (KEYES, 1998;Nikvarz, 2011;Usefy et al, 2010). The life quality scales related to health include physical health (physical health + physical limitation + physical pain + general health) and mental health (social performance + mental problems+ mind health + happiness) (Hatami, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability and validity of the questionnaire of KEYES model was also evaluated (KEYES, 1998;Nikvarz, 2011;Usefy et al, 2010). The life quality scales related to health include physical health (physical health + physical limitation + physical pain + general health) and mental health (social performance + mental problems+ mind health + happiness) (Hatami, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…A similar paper which has studied the relationship between the social well-being and social support among the elderly has concluded that the people's aging is along with the decrease of their social well-being (Usefy et al, 2010). A lot of researches have been done about the life quality of the elderly in different cities of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Também, é o primeiro que avalia a consistên-cia interna do WHOQOL-BREF por meio da confiabilidade composta, ao contrário dos estudos encontrados na literatura que utilizaram o alfa de Cronbach 5,17,20,23,31 . Da mesma forma, avaliou a validade fatorial convergente e discriminante baseada na inspeção da variância média extraída e correlação entre fatores.…”
Section: Geralunclassified
“…abrange o sentido de resistência física/cansaço para as atividades da vida diária, mas também pode ser interpretada pela "sensação de sentirse vivo" 38 . Outros estudos encontraram achados similares para os itens "energia" 23,28,29,31 e "segurança" 20,23,30 . Os itens q5 "aproveitar a vida" e q19 "autossatisfação" apresentaram cargas tanto no seu fator psicológico como em relações sociais e físico 2, respectivamente.…”
Section: Geralunclassified
See 1 more Smart Citation